On a knife-edge c y Sara Brandellero. - Brandellero, Sara Lucia Amelia, 1967- (Oxford : Oxford University Press, 2010)
'On a Knife-Edge' represents the first book-length study in English solely devoted to the work of Joao Cabral de Melo Neto (1920-1999), one of Brazil's foremost poets of the 20th century and a unique voice within Brazilian Modernism.
Description based on print version record.
Includes bibliographical references and index.
Keywords: d